2023
DOI: 10.54536/jtel.v1i2.1814
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty of Reading Comprehension and the Proficiency of the Grade 10 Students of Aloran Trade High School, Philippines

Adones B Cabural,
Elmae Jean S Infantado

Abstract: In the 2018 Program for International Student Assessment (PISA), the Philippines ranked the lowest among the 79 countries participating in the assessment. This study aimed to determine the proficiency of the grade 10 students at Aloran Trade High School and the difficulty of reading comprehension. The instruments used in this study were adapted reading materials from PISA assessments with questions needing subjective answers, categorized according to the different comprehensions proposed in Barrett’s Taxonomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Based on the classroom observation, it was found that students' reading comprehension is influenced by various factors, such as students' personality, attitudes, interests, motivation, and habits. Another factor related to the reading instruction program is the length and difficulty of the material (Cabural & Infantado, 2023). Determining the proper length and difficulty of reading selection for good comprehension is related to the child's age, reading ability, experiential background, and general intellectual abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the classroom observation, it was found that students' reading comprehension is influenced by various factors, such as students' personality, attitudes, interests, motivation, and habits. Another factor related to the reading instruction program is the length and difficulty of the material (Cabural & Infantado, 2023). Determining the proper length and difficulty of reading selection for good comprehension is related to the child's age, reading ability, experiential background, and general intellectual abilities.…”
Section: Discussionmentioning
confidence: 99%